2016
DOI: 10.1111/imj.13281
|View full text |Cite
|
Sign up to set email alerts
|

Elderly patients are at high risk of night‐time admission to the intensive care unit following a rapid response team call

Abstract: Previous studies have shown that elderly patients (age ≥65 years) are less likely to be admitted to the intensive care unit following a rapid response team call and have high hospital mortality rates. This study has shown that elderly patients have a significantly higher probability of being admitted to an intensive care unit following a rapid response team call at night than during the day. However, at no time are they at greater risk than younger patients of incomplete vital sign recording, a failure to esca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Of the 28 included studies, 25 were quantitative, 4,13–36 two were qualitative, 37,38 and one was a mixed‐methods study 39 . Studies with a quantitative design included nine cohort, six case–control, four secondary analyses, three descriptive, two feasibility, and one cross‐sectional study.…”
Section: Results/findingsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 28 included studies, 25 were quantitative, 4,13–36 two were qualitative, 37,38 and one was a mixed‐methods study 39 . Studies with a quantitative design included nine cohort, six case–control, four secondary analyses, three descriptive, two feasibility, and one cross‐sectional study.…”
Section: Results/findingsmentioning
confidence: 99%
“…Studies relevant to the night‐time MET/RRT response showed that this category was either referred to as a MET or an RRT 13–26 . All these studies had been designed using quantitative methodologies that only included observational studies.…”
Section: Results/findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that children under 1 year of age were more likely to have SCD than older children. Older age has been associated with risk for deterioration in adults, emphasising that patients at extremes of age are vulnerable. Despite this increased risk, age is excluded from most early warning score systems .…”
Section: Discussionmentioning
confidence: 99%